Prevalence of nonfunctional overreaching/overtraining in young English athletes - Matos, N. F.; Winsley, R. J.; Williams, C. A. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Nonfunctional overreaching and overtraining (NFOR/OT) in adults can lead to significant decrements in performance, combined with physical and psychological health problems. Little is known about this condition in young athletes by comparison; thus, the aim of the study was to assess the incidence and symptomatology of NFOR/OT in young English athletes. Methods: Three hundred seventy-six athletes (131 girls and 245 boys, age = 15.1 ± 2.0 yr) completed a 92-item survey about NFOR/OT. The sample included athletes competing at club to international standards across 19 different sports. Athletes were classified as NFOR/OT if they reported persistent daily fatigue and a significant decrement in performance that lasted for long periods of time (i.e., weeks to months). Data were analyzed using the Mann-Whitney U and the Kolmogorov-Smirnov nonparametric tests. Significant predictors of NFOR/OT were identified using logistic regression analysis. Results: One hundred ten athletes (29%) reported having been NFOR/OT at least once. The incidence was significantly higher in individual sports (P < 0.01), low-physical demand sports (P < 0.01), females (P < 0.01), and at the elite level (P < 0.01). Training load was not a significant predictor of NFOR/OT; however, competitive level and gender accounted for a small (4.7% and 1.7%, respectively) but significant explanatory variance of NFOR/OT (P < 0.05). Conclusions: Approximately one-third of young athletes have experienced NFOR/OT, making this an issue for parents and coaches to recognize. OT is not solely a training load-related problem with both physical and psychosocial factors identified as important contributors.